Konformitas Teman Sebaya Dengan Delinquency Pada Remaja Kelurahan Dasan Agung, Mataram NTB. - Sarilah; Ani Endriani (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2024)
The aim of this research was to determine the relationship between peer conformity and delinquency in adolescents in the Dasan Agung neighborhood, Selaparang sub-district, Mataram. The data collection method used in this research is a questionnaire as the main method, while interview and documentation methods are complementary methods. The number of samples taken from this research were 30 teenagers from the Head of Dasan Agung Village, Selaparang District, Mataram. whose ages are between 16-22 years. The results of this research show that the results of the t test with a significant value of 0.001, the significant value of variable teenagers in Dasan Agung Village, Selaparang subdistrict, Mataram were rejected, while the alternative hypothesis (Ha) which reads: there is a relationship between peer conformity and juvenile delinquency in Dasan Agung Village Head, subdistrict Selaparang, Mataram was accepted. So there is a relationship between conformity and delinquency in teenagers from the Head of Dasan Agung Village, Selaparang District, Mataram